Gastrointestinal and non-gastrointestinal complication rates associated with diagnostic esophagogastroduodenoscopy under sedation. Issue 19 (13th May 2022) - Jang, Ji Min; Park, Su Bee; Yoon, Jin Young; Kwak, Min Seob; Cha, Jae Myung
Abstract : Abstract: Esophagogastroduodenoscopy (EGD) under sedation may result in gastrointestinal (GI) and non-GI complications. However, no previous studies have reported 30-day GI and non-GI complications after diagnostic EGD under sedation. We conducted a retrospective, observational study of 30-day GI and non-GI complication rates after outpatient diagnostic EGD under sedation in subjects ≥18 years between January 2012 and December 2017 based on a common data model database. Thirty-day complication rates were compared with EGD under sedation or not, type of sedation drugs (midazolam only vs midazolam/propofol) and age groups (18-64 year vs ≥65 year) for GI (bleeding and perforation) and non-GI complications (pneumonia, acute myocardial infarction, congestive heart failure and cerebral stroke). In total, 39, 910 were performed with sedation (midazolam only, n = 16, 033 and midazolam/propofol, n = 23, 864) and 22, 894 were performed without sedation. Elderly patients significantly favored EGD without sedation ( P  < .01). GI and non-GI complication rates were similar between EGD under sedation and without sedation (all P  > .1) except for acute myocardial infarction rate, which was significantly higher in EGD without sedation than EGD under sedation (1.7/10, 000 vs 0.3/10, 000 persons, P  = .043). All GI and non-GI complications were also similar between the midazolam/propofol and midazolam only groups as well as between young and old patients (all P  > .1). Outpatient diagnostic EGD under sedation has an excellent safety profile. In addition, it can be safely performed with midazolam only or midazolam/propofol and in young and old patients.